2001
DOI: 10.1504/ijetm.2001.000739
|View full text |Cite
|
Sign up to set email alerts
|

Organisational mechanisms in environmental management: an evolutionary analysis confronted with empirical facts

Abstract: In this paper we analyse the development of corporate environmental management systems through the core elements of the emerging evolutionary theory of the firm. The environmental management process means a process by which organizations change their structures and cultures as a result of an interlinked effort of individual learning and organizational transformation. We propose that effective environmental management capacities derive primarily from the adaptation of three constitutive mechanisms of firms: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…Llerena (1999) [56] and Avadikyan (2001) [57] indicated that organizational learning and inter-organizational cooperation mechanisms were obviously related to the relationship between environmental management and innovation. Cai and Zhou (2014) [58] found that supply chain integration meant good communication, trust, and cooperation among supply chain members, which had a direct impact on the establishment of supply chain collaboration network and the inter-organizational learning.…”
Section: The Moderating Effect Of Supply Chain Integrationmentioning
confidence: 99%
“…Llerena (1999) [56] and Avadikyan (2001) [57] indicated that organizational learning and inter-organizational cooperation mechanisms were obviously related to the relationship between environmental management and innovation. Cai and Zhou (2014) [58] found that supply chain integration meant good communication, trust, and cooperation among supply chain members, which had a direct impact on the establishment of supply chain collaboration network and the inter-organizational learning.…”
Section: The Moderating Effect Of Supply Chain Integrationmentioning
confidence: 99%
“…In addition to this, van Dijken et al (1999) and Biondi et al (2002) find that environmental orientation of firms, as reflected in the implementation level of environmental management systems is one important determinant for firms' environmentally related innovation activities in small and medium sized firms, which make up an important proportion of the firms' analysed in this paper. Avadikyan et al (2001) point out that EMS act as a coordination mechanism and show based on case studies that EMS implementation can lead to environmental innovation. They also find, that EMS foster team-based approaches.…”
Section: Model Development and Formulation Of Hypothesesmentioning
confidence: 99%
“…Capabilities of the firm, as well as both individual and organizational learning, play significant roles in how an environmental strategy is introduced and implemented (Avadykian et al, 1999;Delmas, 2001;Rennings, 1998). In this context the evolutionary theory of the firm, the resource-based view of the firm and the cumulative model of capabilities are favoured by many authors (Avadykian et al, 1999;Christmann, 2000;Darnall, 2003;Klassen and Whybark, 1999;Rennings, 1998;Russo and Fouts, 1997).…”
Section: Resource-based Viewmentioning
confidence: 99%
“…In this context the evolutionary theory of the firm, the resource-based view of the firm and the cumulative model of capabilities are favoured by many authors (Avadykian et al, 1999;Christmann, 2000;Darnall, 2003;Klassen and Whybark, 1999;Rennings, 1998;Russo and Fouts, 1997).…”
Section: Resource-based Viewmentioning
confidence: 99%